FUNDAMENTAL AND CLINICAL STUDIES ON TA-058 IN THE FIELD OF OBSTETRICS AND GYNECOLOGY - SUGIYAMA, SHUSEI; DOI, SOUNOSUKE; SUGIMOTO, OSAMU; TSUJII, KIYOSHIGE; FUKUDA, YOSHIHIKO; OHTSUKI, KATSUNORI; MAEDA, YOICHI; TSUBOKURA, SHOGO (CHEMOTHERAPY, 1984)
TA-058, a new injectable penicillin, was evaluated pharmacologically and clinically in the field of obstetrics and gynecology. In pharmacological studies, 1 g of TA-058 was intravenously administered to 7 cases prior to simple abdominal hysterectomy, and the concentrations of TA-058 after injection were determined in venous blood, arterial blood of uterus, uterine cervix, portio vaginalis, myometrium, endometrium, oviduct and ovary. The samples were collected during 37 min. to 187 min. after intravenous administration. The venous blood concentration of 4 cases ranged from 2.7μg/ml to 15.9μg/ml and die arterial blood concentration of 6 cases showed from 2.7μg/ml to 28.5 μg/ml. TA-058 was administered to 10 cases of various types of bacterial infections and clinical efficacy was excellent in 5 cases, good in 4 cases and failure in one cases. Overall cure rate was 90.0 %. No side effects nor adverse reactions on clinical laboratory findings in blood and hepatic and renal function were observed.